Crossing Borders: The Impact of the California Tobacco Control Program on Both Sides of the US–Mexico Border - Martínez-Donate, Ana P. (American Public Health Association, 2008)
We examined the association between exposure to the California Tobacco Control Program and tobacco-related behaviors and perceptions among adults of Mexican descent. Three cross-sectional population-based surveys were conducted among adults in cities that represent full, partial, and no exposure to the program: San Diego, Calif, Tijuana, Mexico, and Guadalajara, Mexico, respectively. After we controlled for socioeconomic differences, we found significantly different rates of smoking, exposure to environmental tobacco smoke, and smoking bans in the 3 cities. We also observed a parallel gradient of cross-city differences in theoretical mediators of tobacco control. This suggests a significant association among the California Tobacco Control Program, tobacco-control outcomes, and theoretical mediators of these outcomes. Similar programs should be implemented in other regions; they have widespread effects on social norms and behaviors related to smoking and environmental tobacco smoke and can help achieve tobacco control across nations.